Assessment of bilirubin toxicity to erythrocytes. Implication in neonatal jaundice management. - Brito, MA (2015)
Background Neonatal hyperbilirubinaemia remains one of the most common clinical conditions requiring therapeutic intervention. Nevertheless, reliable indicators of bilirubin toxicity are still missing. This prompted us to investigate (a) the progression o